Motivasi Belajar dalam Pendidikan Islam: Kajian Tafsir Tematik QS. Al-‘Alaq Ayat 1–5 - Avif Alfiyah; Muchacha Aulia Zati Putri (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2026)
A learning motivation is a crucial element that significantly influences the success of the educational process, especially within Islamic education, which views the pursuit of knowledge not only as an academic endeavor but also as an act of worship and a means of human capacity development. This article seeks to explore the concept of learning motivation from the Qur’anic perspective through a thematic exegesis (tafsir maudhu’i) of QS. Al-‘Alaq verses 1–5, as well as to examine its relevance to the advancement of Islamic education in the contemporary context. The study adopts a qualitative approach using library research methods combined with a thematic interpretation framework (maudhu’i). The data are drawn from the Qur’an, classical and modern tafsir works, and relevant literature in Islamic education. The findings indicate that QS. Al-‘Alaq verses 1–5 encompass essential principles of learning motivation, including encouragement to read, the development of literacy culture, enthusiasm for seeking knowledge, spiritual consciousness in learning activities, and the continuous growth of knowledge. The command to read in the opening verse highlights the centrality of intellectual engagement as the foundation of education, while the reference to the qalam (pen) underscores the importance of writing traditions and knowledge preservation. Furthermore, these verses emphasize that effective learning should be rooted in divine values to ensure harmony between intellectual and spiritual dimensions. In conclusion, QS. Al-‘Alaq verses 1–5 are highly relevant in strengthening students’ learning motivation and can be established as a philosophical basis for developing Islamic education that is adaptive, literate, and humanistic.